An Electromyographic Study on the Effects of Bite Planes on Masticatory Muscles: Stabilization Type Bite Plane - HIGASHI, Kazuo; ISHIGAKI, Shouichi; MARUYAMA, Takao; OMAE, Taizou; AKANISHI, Masamitsu; INOUE, Shunji (Journal of the Japanese Society for the Temporomandibular Joint, 1990)
The effects of bite plane on masticatory muscles during tapping and chewing movements were investigated in subjects with no signs and symptoms of stomatognathic dysfunction. Mandibular movements were recorded using a Sirognathograph (Siemens Co.) and electromyograms were simultaneously recorded from masseter, anterior temporalis, posterior temporalis, and anterior digastricus. Two types of bite plane were used for each subject: one for the maxillary arch and the other for the mandibular arch, and additionally, the bite planes were divided into two parts: anterior part and posterior part. The results of this study suggest that the effects of these types of bite plane are different.